Modular design and verification of component-based mechatronic systems with online-reconfiguration. - Giese, Holger
The development of complex mechatronic systems requires a careful and ideally verifiable design. In addition, engineers from different disciplines, namely mechanical, electrical and software engineering, have to cooperate. The current technology is to use block diagrams including discrete blocks with statecharts for the design and verification of such systems. This does not adequately support the verification of large systems which improve the system behavior at run-time by means of online reconfiguration of its controllers because the system as whole has to be verified. It also does not support cooperative interdisciplinary work because a white-box view on all blocks involved in the online reconfiguration is required. This paper proposes a rigorous component concept based on the notion of UML component diagrams which enables modular composition and decomposition of complex systems with online reconfiguration given by hierarchical hybrid component specifications. The approach enables compatibility checks between components that are often independently developed (across the different disciplines) and supports compositional model checking based on a rigorously defined semantics.
Keywords: Software; Software engineering; Design tools and techniques; Modules and interfaces; State diagrams; Software / Program Verification; Model checking; Computing methodologies; Artificial intelligence; Problem solving, control methods and search; Control theory; Design; Languages; Verification; Components; Hybrid systems; Real-time.; Reconfiguration; Unified modelling language (UML).